Chitosan-Pd (II) Complex-Decorated Fe3O4 Nanoparticle as the Highly Effective and Magnetically Recyclable Catalyst for Suzuki and Heck Coupling Reactions. Issue 4 (4th July 2017) - Fakhri, Akram; Naghipour, Ali
Abstract : A novel, recoverable magnetic nanocatalyst for Suzuki and Heck coupling reactions has been successfully prepared by immobilizing chitosan-bound 5-bromosalicylaldehyde Pd (II) complex on the surface of a Fe3 O4 nanoparticle. Structure and composition of the solid catalyst were characterized by Fourier transform infrared (FT-IR), powder X-ray diffraction (XRD), scanning electron microscopy (SEM), inductively coupled plasma atomic emission analysis (ICP-AES), and thermogravimetric analysis (TGA). This nanocatalyst showed high catalytic activity for Suzuki coupling reactions of various aryl halides (I and Br, Cl) and phenylboronic acid in polyethyleneglycol (PEG 400) as an ecofriendly and non-poisonous media. The catalyst also exhibits high activity in a Heck reaction of iodo- and bromoarenes with butylacrylate. Moreover, the nanocatalyst could be separated easily from the reaction mixture by an external magnet and reused four times without obvious loss of catalytic activity. Graphical Abstract: